Globalizing local understanding of fragility in Eurasia. Issue 2 (July 2021) - Kalra, Prajakti; Saxena, Siddharth Shanker
The article aims to introduce the underlying motivation and conceptual underpinning to the special issue entitled "Globalizing Local Understanding of Fragility in Eurasia." The main purpose of this article is to problematize the popular opinion and portrayal of Central Asia (Kazakhstan, Kyrgyz Republic, Tajikistan, Turkmenistan, and Uzbekistan) and more generally the countries of Eurasia and the Caucasus as inherently fragile states which are politically unstable and thus on the brink of collapse. This article also seeks to question narratives of modernity that are singular and constantly out of reach for large swathes of the world's populations because of the narrowness and hegemonic nature of the architecture of global governance. By carefully considering the ways and means through which international institutions categorize countries as fragile and/or failed, the article aims to provide the theoretical foreground for the special issue which focuses on locating inherent community resilience strategies. We explain how the non-participatory norm making behavior of international organizations privilege certain actors, largely the Global North, and simultaneously ignore the majority of Eurasian states. In other words, a demand predicated in the linear evaluation of institutions and norms dictated by global institutions clash with the Eurasian model of inherent complex adaptive capability and introduce fragility. The focus thus is on understanding the 'local' based on the historical analysis of development in the region, nodal points of urban development and community life, forms of social capital, and community resilience strategies in the wider Eurasian region.